2008
DOI: 10.1016/j.jbusvent.2008.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and entrepreneurship development in Russia: A comparative perspective

Abstract: In this paper we use a comparative perspective to explore the ways in which institutions and networks have influenced entrepreneurial development in Russia. We utilize Global Entrepreneurship Monitor (GEM) data to study the effects of the weak institutional environment in Russia on entrepreneurship, comparing it first with all available GEM country samples and second, in more detail, with Brazil and Poland. Our results suggest that Russia's institutional environment is important in explaining its relatively lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
532
2
22

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 646 publications
(580 citation statements)
references
References 49 publications
24
532
2
22
Order By: Relevance
“…In practice, the concentrated financial industrial groups (FIGs) owned by so-called "oligarchs" (Estrin, Poukiakova, & Shapiro, 2009) have been rent-seeking and stifling of entrepreneurship (Aidis, Estrin, & Mickiewicz, 2008) and have conflicting aims with the formal rules of the legal framework and institutions.…”
Section: Russiamentioning
confidence: 99%
“…In practice, the concentrated financial industrial groups (FIGs) owned by so-called "oligarchs" (Estrin, Poukiakova, & Shapiro, 2009) have been rent-seeking and stifling of entrepreneurship (Aidis, Estrin, & Mickiewicz, 2008) and have conflicting aims with the formal rules of the legal framework and institutions.…”
Section: Russiamentioning
confidence: 99%
“…All these behaviors can be encompassed under the rubric of the term 'illegal. Davidson, 1994;Desai and Acs, 2007;Minniti, 2008;Aidis, Estrin and Mickiewicz, 2008;Sobel, 2008;Desai, Acs and Wietzel, 2010;and Douhan and Henrekson, 2010). Douhan and Henrekson (2010) suggest that the foundation of Baumol's classification scheme fails to appreciate the true impact of entrepreneurship in real-world circumstances characterized by institutions and, we suggest, applications and settings, which are suboptimal.…”
Section: Business School Research Into Illegal Entrepreneurshipmentioning
confidence: 91%
“…The aforementioned determinants, both demand and supply side, are relevant for all countries, however, in transitioning economies, their impact on growth and sometimes the vector of a business's development is determined by the features of the institutional environment. The body of empirical research on SME performance in developing economies found a robust relationship between firm performance and the quality of institutions [Aidis et al, 2008;Molz et al, 2009;Blagojevic, Damijan, 2013;Sharafutdinova, Kisunko, 2014;Yukhanaev et al, 2015;Volchek et al, 2013a,b;Wang, You, 2012;Krasniki, Desai, 2016;Welter, Smallbone, 2011]. However, the mechanism behind their interactions remains poorly studied.…”
Section: Determinants and Patterns Of Sme Growth: The Russian Contextmentioning
confidence: 99%
“…Economies that did not manage to develop according to the Western model must operate under an alternative informal institutional network [Smallbone, Welter, 2010], which is prone to rent-seeking, shadow schemes and similarly, tends to incentivize sub-optimal behavior among firms [Golikova, Ermilova, 2006;Sharafutdinova, Kisunko, 2014]. As a result, a discussion of a firm's aspirations for growth, scale of production and performance in transitioning economies without recourse to a study of institutional issues is liable to be incomplete [Aidis et al, 2008;Aidis, 2015;Welter, Smallbone, 2011;Smallbone et al, 2014;Krasniki, Desai, 2016;Wang, You, 2012]. Moreover, an institution-based study has become the main theoretical framework for business research on emerging economies and researchers tend to explore the interplay of formal and informal institutions at multiple levels of analysis [Thorsten et al, 2005;Meyer, Peng, 2005Estrin et al, 2013].…”
Section: Determinants and Patterns Of Sme Growth: The Russian Contextmentioning
confidence: 99%